Award Regulation and the New South Wales Retail Sector, 1971–88: Crisis and Experimentation amidst Changing Models of Development. (1st November 2015) - Heino, Brett
Abstract : The 1970s and 1980s were crucial transitional decades regarding the award regulation of the New South Wales (NSW) retail sector. It was only in 1971–72, at the zenith of the post-World War II model of development known as antipodean Fordism, that the five-day work week was achieved for retail workers. The subsequent crisis of Australian capitalism undermined the basis of the "standard" employment relationship and encouraged the growth of precarious employment forms, such as casual and part-time work, which found particularly strong expression in the retail sector. In the midst of an institutionally entrenched retail union with strong links to the ruling Australian Labor Party (ALP) state government, broader corporatist experimentation, and division in the ranks of retail capital, a new juridic form, the Retail Trade Industrial Tribunal, was created to handle these tensions, an example of "institutional searching" for ways out of deepening crisis. Beset by jurisdictional squabbles with the NSW Industrial Commission and actively undermined by employers, the Tribunal proved an abortive experiment, creating a vacuum into which unadulterated neo-liberal prescriptions would step.